Réponses

2014-05-06T22:50:07+02:00
0,8x + 2y/3 = 2
6x + 5y = 15

0,8x + 2/3y = 2
8/10x =  2 - 2/3y
x = 2 * 10/8 - 2/3y * 10/8
x = 20/8 - 20/24y
x = 5/2 - 5/6y

6x + 5y = 15
6 (5/2 -5/6y) =15
30/2 - 5y = 15
15 - 5 y = 15
-5y = 15 - 15
- 5y = 0
y = 0

0,8x + 2/3y = 2
0,8x + 2/3 (0) = 2
0,8x + 0 = 2
8/10x = 2
x = 2 * 10/8
x = 20/8
x = 4 x 5 / 4 x 2
x = 5/2

Les solutions sont : (5/2 ; 0)

4x + 3y = 11
3x + 4 = 2y

4x = 3y -11
x = 3/4y - 11/4

3x + 4 = 2y
3 (3/4y - 11/4) + 4 = 2y
9/4 y - 33/4 + 4 - 2y = 0
9/4y - 2y = 33/4 - 4
9/4y - 8/4y = 33/4 -16/4
1/4 y = 17/4
y = 17/4 * 4
y = 68/4
y = 17


3x + 4 = 2y
3x + 4 = 2 (17)
3x + 4 = 34
3x = 34 - 4
3x = 30
x = 30/3
x = 3 x 10 / 3 x 1
x = 10
/1
x = 10

Les solutions sont (10 ; 17)